2015
DOI: 10.1007/s00423-015-1324-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment outcomes between nonsurgical and surgical treatment of distal radius fracture in elderly: a systematic review and meta-analysis

Abstract: Surgical and nonsurgical methods produce similar results in the treatment of DRFS in the elderly, and minor objective functional differences did not result an impact on subjective function outcome and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 29 publications
2
64
1
5
Order By: Relevance
“…We found a significant improvement of grip strength in favor of operative treatment, which is in contrast with 2 previous meta-analyses. Ju et al 4 We found no significant difference between treatment groups regarding range of wrist motions.…”
Section: Jama Network Open | Orthopedicsmentioning
confidence: 50%
See 1 more Smart Citation
“…We found a significant improvement of grip strength in favor of operative treatment, which is in contrast with 2 previous meta-analyses. Ju et al 4 We found no significant difference between treatment groups regarding range of wrist motions.…”
Section: Jama Network Open | Orthopedicsmentioning
confidence: 50%
“…[3][4][5] Recent meta-analyses have focused specifically on patient populations 60 years or older. 4,5 These meta-analyses found no difference in functional outcome between operative and nonoperative treatment in elderly patients. However, the international rate of operative treatment of distal radius fractures has been increasing, despite higher cost and limited functional outcome evidence to support this shift.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical treatment of unstable fractures among the elderly has not proven superior to nonoperative treatment regarding functional outcome 64,[113][114][115][116] . However, among an active and slightly younger population (61-80 years), one study has shown a better functional outcome after volar plating compared with non-surgical treatment 117 .…”
Section: Elderly Patientsmentioning
confidence: 99%
“…There had been a few studies of operative versus non‐operative treatment of distal radius fractures in the elderly (over 60 years of age) published recently, but the results were not conclusive . A meta‐analysis showed that surgery and non‐surgical treatment both had their own advantages and disadvantages . The American Academy of Orthopaedic Surgeons guidelines also did not recommend or oppose the surgical treatment of distal radius fractures in patients over 55 years of age .…”
Section: Introductionmentioning
confidence: 99%